2005
DOI: 10.1007/s10717-005-0083-4
|View full text |Cite
|
Sign up to set email alerts
|

Production of Forsterite Powder Using Sol-Gel Technology

Abstract: The effect of initial components, gel-forming additives, and heat-treatment and disaggregation conditions on the completeness of synthesis of forsterite and on powder morphology is considered. The colloid method using silica sol and magnesium acetate solution provides the steadiest and most homogeneous sol and after heat treatment yields highly dispersed powder without additional milling. The technological regimes facilitating complete synthesis are identified. Control of the synthesis temperature makes it pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Magnesium acetate tetrahydrate is widely used as the precursor for the synthesis of magnesium oxide and magnesium containing oxides in the forms of thin film, rode, porous particles with high specific surface area, and so on, where ethanol-mediated sol–gel process and subsequent thermal decomposition of the as-prepared gel are the major chemical processes. For example, Bian et al reported a successful template-free synthesis of mesoporous magnesium oxide via the thermal decomposition of monodispersive crystalline particles of anhydrous magnesium acetate for the application in carbon dioxide adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium acetate tetrahydrate is widely used as the precursor for the synthesis of magnesium oxide and magnesium containing oxides in the forms of thin film, rode, porous particles with high specific surface area, and so on, where ethanol-mediated sol–gel process and subsequent thermal decomposition of the as-prepared gel are the major chemical processes. For example, Bian et al reported a successful template-free synthesis of mesoporous magnesium oxide via the thermal decomposition of monodispersive crystalline particles of anhydrous magnesium acetate for the application in carbon dioxide adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the quality factor of magnesium orthosilicate was found to degrade substantially in the presence of glass impurity and its ultra high quality factor was only achieved when magnesium orthosilicate is synthesized from high purity raw materials [3]. To date, there are several known magnesium orthosilicate powder preparation methods such as aqueous synthesis [12,13], variants of sol-gel technique with different initial materials such as metal alkoxides and hydrated metal salts [1, 14,15] and solid state reaction [16][17][18]. In spite of the wide array of synthesis techniques available, the production of phase-pure magnesium orthosilicate is a challenge and heat treatment at temperatures ranging from 1200 to 1600°C are often required to obtain pure magnesium orthosilicate [13].…”
Section: Introductionmentioning
confidence: 99%
“…Powders were prepared by the sol-gel method based on magnesium acetate and silica sol (colloidal solution of amorphous silicon oxide) by technology developed previously [4]. The magnesium oxide content was varied within the limits from 63 to 37%, including the stoichiometric composition of forsterite (Table 1 and 2).…”
mentioning
confidence: 99%